2018
DOI: 10.1007/s00441-018-2820-3
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic susceptibility to neuroblastoma: current knowledge and future directions

Abstract: Neuroblastoma, a malignancy of the developing peripheral nervous system that affects infants and young children, is a complex genetic disease. Over the past two decades, significant progress has been made toward understanding the genetic determinants that predispose to this often lethal childhood cancer. Approximately 1-2% of neuroblastomas are inherited in an autosomal dominant fashion and a combination of co-morbidity and linkage studies has led to the identification of germline mutations in PHOX2B and ALK a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 189 publications
(236 reference statements)
0
74
0
Order By: Relevance
“…Like other embryonal malignancies, neuroblastoma is thought to be primarily a genetic disease which can be divided into familiar or sporadic with ~1%–2% of cases are inherited 31. The first significant insight into the genomic lesions driving the development of neuroblastoma was the observation in the middle of 1980 that amplification of the MYCN oncogene in neuroblastoma is associated with clinically aggressive disease and poor prognosis 6 7 31. In 2008, a large genetic linkage study in families with neuroblastoma identified a linkage signal at chromosome 2p23–24.…”
Section: Discussionmentioning
confidence: 99%
“…Like other embryonal malignancies, neuroblastoma is thought to be primarily a genetic disease which can be divided into familiar or sporadic with ~1%–2% of cases are inherited 31. The first significant insight into the genomic lesions driving the development of neuroblastoma was the observation in the middle of 1980 that amplification of the MYCN oncogene in neuroblastoma is associated with clinically aggressive disease and poor prognosis 6 7 31. In 2008, a large genetic linkage study in families with neuroblastoma identified a linkage signal at chromosome 2p23–24.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma is genetically heterogeneous ( 8 ). Lately, intensive research has led to dramatic discoveries of some causal heritable mutations in familial neuroblastoma ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings raise the fundamental question of why some children develop neuroblastoma, and what predisposing genetic factors may be present in these patients. Due to the inherent limitations of candidate gene and family association studies, this question could not be addressed until the development of genotyping arrays and high-performance computing allowed researchers to conduct Genome-wide association studies (GWAS) to identify germline genetic variation that may lead to development of neuroblastoma [ 83 ]. A summary of germline GWAS variants predisposing to neuroblastoma can be seen in Table 2 .…”
Section: Sporadic Neuroblastomamentioning
confidence: 99%